Overuse of medical imaging and effects of payer-provider integration: quasi-experimental evidence from Finland - Konsta Lavaste (Health Economics Review)
Abstract Background Healthcare expenditures have risen in middle- and high-income countries. One of the potential contributors is the overuse of diagnostics. I explore whether medical imaging is overused when privately owned clinics in Finland treat patients with voluntary private health insurance (VPHI). Methods I employ administrative insurance claims data from a major Finnish insurance company, covering 2016–2019, and exploit two market entries of clinics owned by the company in 2017. The underlying assumption is that the insurance company’s own clinics had weaker incentives to overuse imaging than other privately owned clinics because the payer and the provider belonged to the same entity. I identify the overuse using the staggered difference-in-differences (DID) strategy, in which I consider patients from cities with a market entry as the treatment group and compare them to patients in other similar cities. Results I find that the market entries decreased the use of radiography and ultrasound imaging in the treatment of VPHI policyholders, suggesting that private clinics overused these imaging technologies. The more expensive computed tomography (CT) and magnetic resonance imaging (MRI) were, however, not overused. Conclusions The results show that private clinics in Finland overused some imaging technologies when treating VPHI policyholders. The extent and magnitude of overuse can, however, vary considerably between imaging technologies and medical ailments.